Text Mining and News Sentiment Analysis of the PPRT (Domestic Worker Protection) Bill in Three Online News Media From 2004 to 2024 - Dian Novita Kristiyani; Richard Gordon Mayopu (UIN Sumatera Utara, 2025)
The Domestic Worker Protection Bill (RUU PPRT) has been a critical issue in Indonesia, yet its legislative process has stagnated for two decades, leading to intense public discourse. This study aims to analyze the sentiment and narrative dynamics of RUU PPRT news coverage in online media, as well as the media's role in shaping public opinion. Employing a Text Mining and Lexicon-Based Sentiment Analysis approach, enhanced with adaptations for the Indonesian lexicon, this research analyzes 387 news articles from three prominent online media outlets (Tempo, Kompas, and VOA News) published between 2004 and 2024. The findings reveal that positive sentiment dominates with 58.1%, followed by negative sentiment at 31.3%, and neutral sentiment at 10.6%. Tempo was identified as the most active media outlet covering this issue. These results indicate that the mass media plays a significant role in shaping the pattern of public discourse regarding the PPRT Bill, particularly through the dominance of positive sentiment in its reporting and confirm that lexicon-based sentiment analysis can systematically capture the dynamics of complex socio-political narratives.